Gender, Power and Political Will: Tensions Between Domestic Policy and International Commitments in Gender Mainstreaming in Costa Rica (2018-2024) - Calvo Valerio, Gaudy (2025)
Gender equality experiences both progress and setbacks at the national and international levels. It has nevertheless become a normative principle of global governance, promoted and materialized through international instruments such as the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), the Beijing Platform for Action, and the 2030 Agenda for Sustainable Development. However, the integration and implementation of these commitments at the national level reveal persistent tensions between international discourse and the institutional practices of States. The objective of this article is to analyze how internal power structures condition the fulfillment of international gender equality regimes, using Costa Rica as a representative case study. Drawing on the doctoral research Analysis of Political-Institutional Dissonances in Gender Mainstreaming: The Case of Public Policies in Costa Rica (2018–2024) (Calvo, 2025), it examines the gap between the international commitments assumed by the Costa Rican State and the effectiveness of its national public policy on gender equality, focusing on the implementation of the National Policy for Equality and Gender Equity (PIEG 2018–2030). The article is based on a theoretical-critical analysis that connects domestic politics with the international human rights system, through a qualitative approach. The theoretical framework integrates contributions from Feminist International Relations theory, Social Constructivism, Neoinstitutionalism, and Feminist Foreign Policy, to explain how international gender equality norms are created, diffused, and internalized, and how these dynamics are mediated by power relations and the institutional capacities of States. The results show that political-institutional dissonances—conceptual, normative, structural-administrative, symbolic-discursive, cultural-subjective, organizational-governance, and technical-methodological—reflect the tension between the country’s international legitimacy and the limitations of its state structure in achieving coherent compliance with multilateral commitments. The article concludes that gender mainstreaming in Costa Rica’s public policies is a political process conditioned by power relations and institutional culture, in which political will emerges as a key variable for institutional transformation and for ensuring coherence between domestic policy and international projection. This study contributes to the field of International Relations by positioning gender equality as a central axis for analyzing power, legitimacy, and global governance.